Culture and Stock Price Clustering: Evidence from The Peoples' Republic of China - Brown, Philip; Mitchell, Jason (2012)
Price clustering is the tendency of prices to be observed more frequently at some numbers than others. It results from human bias and from haziness or imprecise beliefs about underlying value. To many Chinese, the number 8 is attractive because it is considered "lucky", while 4 is "unlucky" and to be avoided. We conduct a tightly controlled experiment to determine whether a culturally heuristic number preference exists, by studying trading on the Shanghai and Shenzhen stock exchanges, which historically have been relatively segmented along cultural lines. Our results are extremely clear. For much of our sample period (1994-2002), the prices of A-shares (mostly held by Chinese organisations or individuals) traded on the Shanghai stock exchange were more than twice as likely to end in 8, than 4. Similarly, for A-shares traded on the Shenzhen stock exchange a preference for 8 was found. Preference for 8 on both exchanges was initially very strong, but has weakened somewhat over time. It is observed in opening, high and low as well as closing prices, reinforcing its pervasiveness. Overall, the cultural preference manifest in the prices of A-shares is widespread in both markets and its presence is accentuated once other factors that influence price clustering are taken into account. The preference for 8 was much weaker for B-shares, which largely have been held by foreigners.